Evaluation of the H.O.P.E. Project - McCarty, Melanie (My University, 2020)
The main goal of The Health Opportunities through People Empowerment (HOPE) project is to advance health equity by organizing and providing residents training and support for community organizing, focused in the Northview neighborhood of Manhattan, Kansas. More specifically, “the focus is to improve health and equity through policy, system, environmental, and personal change”. The project began in 2017, shortly after a community needs assessment revealed health disparities were prominent in the Northview area of Manhattan, Kansas. The project was funded by the Kansas Health Foundation and led by the Flint Hills Wellness Coalition (FHWC). The purpose of the current project was to evaluate community-organizing aspects of the HOPE project by assessing the perception of community residents regarding the strengths of community involvement in this neighborhood health program. This applied practical experience (APE) with the FHWC seeks to improve health by engaging with residents in local communities throughout Manhattan and Riley County. Within the FHWC, I was mentored by Brandon Irwin, PhD. Dr. Irwin was the Community Liaison within the H.O.P.E. project. His background includes Kinesiology and he works at the community level to promote health and wellness to residents throughout Manhattan, with a specific focus on the Northview Neighborhood. Evaluation of community organizing aspects of the HOPE Project was conducted through the use of Appreciative Inquiry theory (Coghlan et al., 2003) and guided by the following questions: 1) What is working? 2) What needs changed? 3) What is most important for resident-led community organizing? and 4) How well did outcomes align with or represent the HOPE project Theory of Change? The methods included individual interviews with project team members, involved residents, and key influencers. The analysis process utilized a data matrix to identify themes. The findings suggest that the HOPE project is working to increase community organization and engagement. Results show that the project is successfully encouraging social neighborhood connectedness, discussions of shared interests between residents, and project ownership and leadership. Some challenges of the work include increasing the number of people involved, demographic diversity within residents, and financial sustainability.
Keywords: community organizing; equity; health disparities